Marketing of Pig and Pork in Meghalaya - Suchiang, R.; Ray, M. N.; Bora, L.; Payeng, S.; Chanu, S. N.; Langstang, F. E. (Indian Journal of Hill Farming, 2018)
A study was conducted in two purposively selected districts of Meghalaya viz. East Khasi Hills District and West Khasi Hills District in order to find out the marketing channel of pigs, mode of marketing of pork and the source of piglet supply. Fifteen pig farmers were selected from each of the eight selected villages from the study area to make a sample size 120. The study revealed that majority (72.5 percent) of the farmers disposed their pigs through local traders followed by 25 percent through retailers and only a meagre 2.5 percent disposed their pigs directly to consumers. In respect of pork majority of them (68.3%) disposed to the local traders followed by 10% at the local market, 9.17% at home, 6.67% during social occasion and only 5 percent disposed their pork to the butchers. On the other hand so far as supply of piglet was concerned, majority (77.5%) of the respondents bought their piglets from co-farmers and 22.5% bought their piglet from market.